Pengaruh Penggunaan Media BAPER Terhadap Kemampuan Numerasi Siswa SDN 80 Liangbai - Nur Isra (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2024)
The purpose of this study was to find out that the use of multiplication rod media (BAPER) had a positive effect on the mathematical numeracy abilities grade students of class IV UPTD SD Negeri 80 Liangbai. This type of is a quasi- eksperimental research (quasi-eksperimental) involving the control class and the eksperimental class with a nonequivalent control group design. The variables studied in this study were the mathematical numeracy abilities grade students of class IV UPTD SD Negeri 80 Liangbai as the dependent variable and the use of BAPER media as the independent variable. The population of this research is the grade students of class IV UPTD SD Negeri 80 Liangbai in the odd semester of the 2022/2023 academic year which consists of two classes. The sample of this class IV A and class IV B, each of which consisted of fifteen students obtained using a saturated sample. The research data was obtained using a research instrument in the form of a student’s mathematical numeracy ability test. Based on descriptive statistical analysis, it was obtained that the average value of student’s numeracy skills in the control class for posttest data was 70.00 with medium ability category and standard deviation of 6,503 while in the experimental class the average value of student’s numeracy abilities for posttest data was 80.27 with medium ability category and standars deviation of 5,934 and the inferential using the test of the large effect of the treatment obtained the value of r2= 0,19 with a percentage of 19% which is in the category of medium effect anda has an effect on student’s numeracy abilities. so it can be concluded that the use of multiplication rod media (BAPER) has a positive effect on the numeracy skills grade of IV UPTD SD Negeri 80 Liangbai.